PUSAT PELATIHAN BAHASA UNIVERSITAS TANJUNGPURA - Janice Zaneta; Tri Wibowo Caesariadi; Hamdil Khaliesh (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2021)
Mastery of foreign languages is an important skill to compete in the international world in the future. The Language Unit of Universitas Tanjungpura also supports the mastery of foreign languages and has a vision and mission to become a center for international language education and services in West Kalimantan. With the development of Universitas Tanjungpura, Universitas Tanjungpura currently has BLU status, so educational facilities need to provide commercial areas to fulfill this BLU status. Therefore, an Universitas Tanjungpura Language Training Center is needed that can support foreign language learning and there is a commercial area. The design location is located on Daya National Street, Sea Bansir, Southeast Pontianak Subdistrict, Pontianak City, West Kalimantan, with an area of ±11,000 m2. The design uses a comparison method between the results of site observations, existing buildings, literature studies, with training center standards, as well as analyzing internal and external aspects of the site. The basic idea of interior and exterior spatial planning is to support foreign language learning and attract visitors to have activities at the Universitas Tanjungpura Language Training Center. This is realized by designing an educational space that meets the criteria for a training room, a commercial space that has a selling value, and a public zone that is free to be visited by the public. The appeal of the idea of a design building is a triangle which is the hallmark of the Universitas Tanjungpura building form. The building is covered with secondary skin with a typical pattern of the Universitas Tanjungpura.